Indicação Geográfica na vitivinicultura como estratégia para o desenvolvimento local e valorização de territórios: Análise da experiência ibérica (Portugal e Espanha) e da Serra Gaúcha (estado do Rio Grande do Sul - Brasil) - Teodoro, Vitor Bini (2024)
The process of globalization has intensified competition and escalated agro-industrial production, with a strong expansion of agricultural commodities. Nevertheless, new market niches and consumers have also emerged, seeking differentiated and quality-recognized products. In this context, Geographical Indications arise, being a recognized registration conferred upon products or services that are characteristic of their region of origin, attributing to them reputation, intrinsic value, and their own identity, distinguishing them from similar ones available in the market. These are products that present a unique quality due to natural resources such as soil, vegetation, climate, and craftsmanship. In this sense, belonging to a demarcated region can become a means of integrating peripheral regions and small municipalities into the competitive agri-food market, providing their respective local populations with a solution for local development, the central hypothesis of this study. Thus, the present study sought to identify, in the selected countries (Brazil, Spain and Portugal), to understand the development of their respective geographical indications circumscribed in wine regions, in a comparative perspective, whether belonging to a region demarcated enabled the local development of these locations. It can be concluded that belonging to a demarcated region sharpens curiosity about the local peculiarity, providing relevant gains for the localities, as long as the actions occur in a cooperative and articulated way, between the Public and Private Power and Civil Society, being able to promote progressively achieve socioeconomic inclusion and improve the quality of life for their respective populations.